2011
DOI: 10.1186/1479-5868-8-98
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of sedentary behaviour and health indicators in school-aged children and youth

Abstract: Accumulating evidence suggests that, independent of physical activity levels, sedentary behaviours are associated with increased risk of cardio-metabolic disease, all-cause mortality, and a variety of physiological and psychological problems. Therefore, the purpose of this systematic review is to determine the relationship between sedentary behaviour and health indicators in school-aged children and youth aged 5-17 years. Online databases (MEDLINE, EMBASE and PsycINFO), personal libraries and government docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

70
1,438
17
109

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,628 publications
(1,634 citation statements)
references
References 246 publications
70
1,438
17
109
Order By: Relevance
“…In large-scale cohort studies, self-reported time spent watching TV is usually used as a proxy marker of sedentary behaviour. Recent reviews (40)(41)(42) have concluded that TV-viewing is significantly associated with obesity and body fat, although one of these reported that this association was not likely to be clinically relevant (40) . However, few of the studies included in these reviews adjusted their analyses for objectively measured physical activity.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…In large-scale cohort studies, self-reported time spent watching TV is usually used as a proxy marker of sedentary behaviour. Recent reviews (40)(41)(42) have concluded that TV-viewing is significantly associated with obesity and body fat, although one of these reported that this association was not likely to be clinically relevant (40) . However, few of the studies included in these reviews adjusted their analyses for objectively measured physical activity.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…A similar result was found in a study by Fotti et al 6 , in which adolescents who spent longer hours in front of the PC were less likely to have insufficient hours of sleep (> 8 hours). The relationship between excessive body time with excess body fat and insufficient hours of sleep/day is established in the literature 6,14,15 . However, when investigating PC time and the combination of conditions (excess body fat and hours of sleep), it can be observed that the cut-off point adopted for such classification in relation to excessive use of PC (≥ 2 hours) only identified alterations in relation to the number of hours of sleep and not in relation to body fat 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar questions addressing the time of screen use were used in international studies 14 , with good reliability and reproducibility in Brazilian adolescents (CI = 0.76; 95% CI: 0.70-0.81; kappa = 0.52) 24 .…”
Section: Independent Variablesmentioning
confidence: 99%
See 2 more Smart Citations